Evolution of the United States Military Extracorporeal Membrane Oxygenation Transport Team. Issue 11 (30th December 2020) - Read, Matthew D; Nam, Jason J; Biscotti, Mauer; Piper, Lydia C; Thomas, Sarah B; Sams, Valerie G; Elliott, Bernadette S; Negaard, Kathryn A; Lantry, James H; DellaVolpe, Jeffry D; Batchinsky, Andriy; Cannon, Jeremy W; et al.
Abstract: Introduction: The use of extracorporeal membrane oxygenation (ECMO) for the care of critically ill adult patients has increased over the past decade. It has been utilized in more austere locations, to include combat wounded. The U.S. military established the Acute Lung Rescue Team in 2005 to transport and care for patients unable to be managed by standard medical evacuation resources. In 2012, the U.S. military expanded upon this capacity, establishing an ECMO program at Brooke Army Medical Center. To maintain currency, the program treats both military and civilian patients. Materials and methods: We conducted a single-center retrospective review of all patients transported by the sole U.S. military ECMO program from September 2012 to December 2019. We analyzed basic demographic data, ECMO indication, transport distance range, survival to decannulation and discharge, and programmatic growth. Results: The U.S. military ECMO team conducted 110 ECMO transports. Of these, 88 patients (80%) were transported to our facility and 81 (73.6%) were cannulated for ECMO by our team prior to transport. The primary indication for ECMO was respiratory failure (76%). The range of transport distance was 6.5 to 8, 451 miles (median air transport distance = 1, 328 miles, median ground transport distance = 16 miles). In patients who were cannulated remotely, survival to decannulation was 76% and survival to discharge was 73.3%. Conclusions: Utilization of the U.S. military ECMO team has increased exponentially since January 2017. With an increased tempo of transport operations and distance of critical care transport, survival to decannulation and discharge rates exceed national benchmarks as described in ELSO published data. The ability to cannulate patients in remote locations and provide critical care transport to a military medical treatment facility has allowed the U.S. military to maintain readiness of a critical medical asset.